Senderización y Señalética de la Ciclo Ruta Turística Saraguro – La Papaya en el Cantón Saraguro de la Provincia de Loja - Rohoden Jaramillo, Kevin Edgar (2017)
Tourism focuses on the economic development of our country, because it retains a great natural and cultural richness together with its attractions, traditions, customs, cuisine, etc. It is one of the most important in generating employment to population factors. Within regions containing the Ecuador, we find the Sierra region, characterized by its breathtaking mountain ridges, volcanoes and glaciers, just several national parks and nature reserves exist that have a very diverse flora and fauna; within this region we can find the Province of Loja has sixteen cantons, including the Saraguro canton, renowned for its rich culture and communities which offer the realization of the activity of Community Tourism towards tourists is visiting this canton. These tourist activities are improved by means of the correct signaling that exists in the different roads or roads leading to the attractions. Taking the criterion that the signage is the part of the science of the visual communication that studies the functional relations between the signs of orientation in the space and the behavior of the individuals, therefore it studies the use of graphic signs to guide the flow of persons in a given space and informs of the available services, it is considered convenient to use the established in Manual Corporativo de Señalización Turística del MINTUR and which works to achieve an adequate orientation, information and security system, based on the installation of Efficient tourist signaling systems of great utility for visitors and mobility in general. For this reason, having established a manual in advance, it is considered appropriate to take into account the same for the realization of this project, based on its methodology and regulation. In this research work is to improve and significantly increase tourism in the parish, for this reason it was thought advisable to carry out the thesis project called "Senderización and Señalética of the Cycle Tourist Route Saraguro - La Papaya on the Saraguro canton of the Province of Loja "the primary objective the conservation, protection and knowledge of the natural attractions through the implementation of senderización and tourist signs, also promote cycling that through thereof come to know various natural attractions and cultural existing in the sector, an issue that now has become of great interest at the national and global levels. To develop research efficiently was taken as general objective: "To develop the proposal and Señalética and Senderización the Cycle Tourist Route Saraguro - La Papaya on the Saraguro canton of the Province of Loja". Its three specific objectives were: "Making the tourist diagnosis of the current situation of the Cycle Tourist Route Saraguro-La Papaya on the Saraguro canton of the Province of Loja"; "Propose Senderizacion and Señalética of the Cycle Tourist Route Saraguro-La Papaya on the Saraguro canton of the Province of Loja"; and finally "Identify the significant environmental impacts of the project in stages." 5 In terms of methodology this was developed based on the fulfillment of each of the proposed objectives, and these different methods and techniques applied. For the first objective was used to analytical, synthetic method and technique of direct observation to each of the attractions compliance with the regulations of the Ministry of Tourism, further interviews was conducted with the current charge of tourism activities Canton, with manager of the Hacienda La Papaya and a resident of Canton also the matrix of tourist attractions MINTUR was used to validate the hierarchy that is each of them, the SWOT analysis the author Carla Ricaurte who helped us was also applied to highlight the situation of the attractions mentioned above and to obtain sufficient and necessary information; thus achieving achieve accurate accordingly to take related measures to needs diagnosis. As for the second objective, the inductive and deductive methods were used, which allowed to study the characteristics of the place and to support with the respective conclusions and proposals that count with technical criteria in the tourist aspect with the only purpose of serving for the benefit of the attractions and the community, in addition the present project was regulated to the norms constituted in the Corporative Manual of Signaltics of the Ministry of Tourism, finally was counted on the support of a GPS to be able to obtain the geographic coordinates intended in the elaboration of the respective route cycle. For the third and final goal Leopold Matrix (Cause and Effect) was used, the same that was used to identify the initial impact of the project in their natural environment and identify the percentage of environmental impacts at different stages of the project. It can be said that Saraguro parish has a great variety of natural and cultural tourist attractions, having the same important qualities to promote tourism development, these need to be strengthened by the relevant authorities and inhabitants of the sector. It should be mentioned that some of the attractions and existing roads lack signs that allow the tourist to guide in a correct and safe way.